Solvent-Driven Chirality Switching of a Pillar[4]arene[1]quinone Having a Chiral Amine-Substituted Quinone Subunit - Liu, Chunhong; Yu, Zhipeng; Yao, Jiabin; Ji, Jiecheng; Zhao, Ting; Wu, Wanhua; Yang, Cheng (Frontiers in Chemistry, 2021)
Several new chiral pillar[4]arene[1]quinone derivatives were synthesized by reacting pillar[4]arene[1]quinone (EtP4Q1), containing four 1,4-diethoxybenzene units and one benzoquinone unit, with various chiral amines via Michael addition. The chirally modified pillar[4]arene[1]quinons showed unique chiroptical properties, giving anisotropy factors of the charge transfer up to -0.018. Intriguingly, the chiroptical properties could be switched by the use of different solvents.